BOND STRENGTH OF CONCRETE WITH THE REINFORCEMENT BARS POLLUTED WITH OIL - Ismaeel H.Musa Albarwary; James H. Haido (European Scientific Journal, ESJ, 2013)
Practically, the concrete is usually cast in forms made from wood or steel. These forms are oiled to avoid their adhesion with the hardened concrete material. The reinforced steel bars may be polluted with the oil when they placed over or inside the forms. This pollution may affect the bond between the steel bars used and concrete and consequently the strength of reinforced concrete members will decrease. In present investigation, the bond strength of the oil polluted steel bars with concrete was studied. Tests were conducted on 72 cylindrical concrete specimens with compressive strength of 24 MPa at age of 28 days. Two embedded lengths of steel bars were considered in present tests namely 30 cm and 15 cm with four bar diameters. Based on the current experimental results, it is concluded that the pollution of steel bars with oil does not affect their bond strength if the embedded length of the bars is increased and their diameters are decreased. For these bars the bond strength is greater than the tensile strength. It is observed that the embedded length of the bar inversely affects the deterioration of the bond strength due to the bar pollution. For the polluted and non polluted bars it can be stated that small bar sizes has greater bond strength than large bar sizes if the embedded length is small. The predominant type mode of failure is splitting mode for all the tested specimens and no slip failure occurred in testing all the polluted and non-polluted bars throughout the experiments.